Cellulose degradation by Leucocoprinus gongylophorus, the fungus cultured by the leaf-cutting ant Atta sexdens rubropilosa - Bacci, M. [UNESP]; Anversa, M. M. [UNESP]; Pagnocca, F. C. [UNESP] (Springer Nature, 1995)
Leucocoprinus gongylophorus, the fungus cultured by the leaf-cutting ant Atta sexdens rubropilosa, is able to degrade efficiently cellulose, microcrystaline cellulose, carboximethylcellulose, and cellobiose. Analysis of the degradation products indicate that the fungus produce extracellular β-glucosidase, exo- and endo-glucanase. The importance of cellulose degradation to the association of fungus and ant is discussed.
Keywords: Atta sexdens rubropilosa; Cellulose; Leaf-cutting ant; Leucocoprinus gongylophorus; beta glucosidase; carboxymethylcellulose; cellobiose; cellulose; glucan synthase; ant; biodegradation; controlled study; fungus culture; nonhuman; plant leaf; priority journal; Agaricales; Animal; Ants; beta-Glucosidase; Biodegradation; Carboxymethylcellulose; Cellobiose; Cellulase; Support, Non-U.S. Gov't; Atta; Formicidae; Fungi; Leucocoprinus